Can Li atoms anchored on boron- and nitrogen-doped graphene catalyze dinitrogen molecules to ammonia? a DFT study - Verma, Tushar Singh; Samal, Pragnya Paramita; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (ChemPhysChem, 2023)
The most successful electrochemical conversion of ammonia from dinitrogen molecule reported to date is through a Li mediated mechanism. In the framework of the above fact and that Li anchored graphene is an experimentally feasible system, the present work is a computational experiment to identify the potential of Li anchored graphene as a catalyst for N-2 to NH3 conversion as a function of (a) minimum number of Li atoms needed for anchoring on graphene sheets and (b) the role of chemical modification of graphene surfaces. The studies bring forth an understanding that Li anchored graphene sheets are potential catalysts for ammonia conversion with preferential adsorption of N-2 through end-on configuration on Li atoms anchored on doped and pristine graphene surfaces. This mode of adsorption being characteristic of Nitrogen Reduction Reaction (NRR) through enzymatic pathway, examination of the same followed by analysis of electronic properties demonstrates that tri-Li atoms (Tri Atom Catalysts, TACs) are more efficient as catalysts for NRR as compared to two Li atoms (Di Atom Catalysts, DACs). Either way, the rate determining step was found to be *NH2 ->*NH3 step (mixed pathway) with Delta G(max)=1.02 eV and *NH2-*NH3 ->*NH2 step (enzymatic pathway) with Delta G(max)=1.11 eV for 1B doped TAC and DAC on graphene sheet, respectively. Consequently, this work identifies the viability of Li anchored graphene based 2-D sheets as hetero-atom catalyst for NRR.
Keywords: computational chemistry; Graphene Sheet; heterogeneous catalysis; Li Nanoparticles; Nitrogen Reduction Reaction

Computational identification of most potent atom pair catalysts for electrocatalytic nitrogen reduction reaction over hydrogen evolution reaction - Verma, Tushar Singh; Dar, Afshana Hassan; Dar, Manzoor Ahmad; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Inter., 2024)
Robust electrocatalytic atom pair compositions (APCs) where Nitrogen Reduction Reaction (NRR) is more enhanced over competing Hydrogen Evolution Reaction (HER) is searched for using computational studies based on Density Functional Theory based methods. Atomic pairs are anchored on mechanically and thermally stable graphene surfaces. A wide range of transition metal based atom pair compositions from 3d, 4d, and 5d groups are systematically investigated for reduction of dinitrogen molecule with lower reduction barrier as compared to HER. APR compositions of Ni-Rh with an overall limiting potential of -0.22 V, Fe-W with an overall limiting potential of -0.26 V and Co-Pt with an overall limiting potential of -0.28 V are identified as the most potent atomic pairs for enhanced nitrogen reduction reaction over the HER. Finally, the performance of most potent composition, viz., Ni-Rh is validated to be consistent with respect to their thermodynamic stability and performance within the solvent effects.
Keywords: Atom pair catalysts; Density Functional Theory (DFT); Electrochemical nitrogen reduction reaction (eNRR); hydrogen evolution reaction (HER); IR stretching frequencies; N-N bond length